ANTIGENIC ACTIVITY ASSAYS OF EXPERIMENTAL CONJUGATE VACCINES BASED ON SYNTHETIC OLIGOSACCHARIDE LIGANDS AND CRM197 CARRIER PROTEIN - E. G. Bogomolova; O. A. Dodrovolskaya; E. A. Fedorova; A. M. Kondrashkina; N. N. Kolmakov; S. A. Ishchuk; I. V. Dukhovlinov; A. S. Simbirtsev (Медицинская иммунология)
So far, there is no effective treatment for a number of socially significant bacterial and fungal diseases. β-(1→3) glucans are polysaccharides consisting of glucose units linked together with β-(1→3)- glycoside bonds. They are principal components of the fungal cell wall including such dangerous nosocomial pathogens as Candida albicans, Aspergillus fumigatus and others. At the same time, β-(1→3) glucans are absent in humans and other mammals, thus making them to be promising components of carbohydrate-protein conjugate vaccines for prevention and treatment of fungal infections. The CRM197 protein is a non-toxic derivative of diphtheria toxin, which is widely used as a safe carrier for conjugate vaccines. The CRM197 extraction from lysogenic C. diphtheriae cultures is a classic way of its production. An alternative to the classic method is a transgene-driven CRM197 protein expression in E. coli, B. subtilis and Pseudomonas fluorescens. The advantage for using Escherichia coli in this case is that this method is more simple and inexpensive, and allows of producing recombinant CRM197 within short terms employing a non-pathogenic microorganism. The purpose of this study was to investigate antigenic activity in the samples of experimental conjugate vaccines based on synthetic oligosaccharide ligands and CRM197 carrier protein, by means of a competitive ELISA. A double immunization of laboratory Balb/c mice with experimental samples of conjugate vaccines based on oligosaccharide ligands and CRM197 protein caused induction of specific antibodies at high titers. All the samples of oligoglucoside-based conjugate vaccines with different contents of monomeric units (pentasaccharides, heptasaccharides, nanosaccharides, and undecasaccharides) caused the formation high antibody titer at the level 1: 51,200,following tandem injections. High avidity of antibodies to their oligosaccharide ligands was shown by competitive ELISA reaction. These data suggest a relevance of further pre-clinical trials of conjugate vaccines against Candida and Aspergillus, as well as selection of the most immunogenic and effective version of the conjugate vaccine.